Bolivia Social Accounting Matrix, 1996 - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The 1996 Bolivia Social Accounting Matrix (SAM) permits a meaningful and detailed analysis of the productive structure of the economy as well as alternative trade reforms and income distribution channels. Agricultural activities are further disaggregated into agriculture and livestock production. Manufactures are disaggregated into multiple sectors and products in order to identify export manufacture. Labor is disaggregated according to skill, and type of occupation, while households are classified according to geographical location (urban vs. rural). Taxes are differentiated into income, sales and tariffs. Finally, the accompanying paper describes both the macroeconomic and microeconomic SAMs, paying special attention to a careful documentation of data sources, assumptions, and balancing methods.